Analysis of Factors Influencing Sustainable Intentions for The Use of Artificial Intelligence Technology in Indonesia: Integration of The Technology Acceptance Model And Theory of Planned Behavior - Sarah Adelina Jusak; Angela Caroline; Agus Gunawan; Yoke Pribadi Kornarius (Jurnal Syntax Admiration, 2025)
This study examines in depth the factors influencing the sustainable intention to use Artificial Intelligence (AI) technology among professionals in Indonesia. By integrating the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), this study aims to identify and analyze the key determinants driving the continued use of AI in the workplace. Using a quantitative approach, data were collected through an online survey involving 113 respondents actively using AI across various industry sectors and analyzed using structural equation modeling (SEM). The results indicate that perceived usefulness, perceived ease of use, and subjective norms have a significant positive effect on the intention to continue using AI. Notably, perceived usefulness emerged as the strongest predictor, highlighting the critical role of AI's practical value in encouraging sustained use. In addition, perceived behavioral control significantly influences sustainable intention, underscoring the importance of organizational support and skill development in facilitating long-term AI adoption. These findings contribute to the theoretical development of technology acceptance in professional settings and offer practical insights for organizations aiming to enhance AI integration strategies.